2021
DOI: 10.1039/d1nj02701h
|View full text |Cite
|
Sign up to set email alerts
|

Cochineal quinone carbon dot synthesis via a keto–enol tautomerism strategy and their intermolecular photo-induced cross-redox interactions with tetracycline

Abstract: Natural products originated carbon dots promising a charming and valuable platform for bio-fluorescence probes, however, application scope of these probes was seriously restricted, due to the indistinct molecular structures of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Next, radical inhibition experiments were conducted in the presence of a stable oxyl-radical, 2,2,6,6-tetra-methyl-1-oxylpi-peridine (TEMPO) (Scheme 4D). 44 The results of these experiments showed that the electrocatalytic halogenation and dimer condensation processes were inhibited, indicating that a halogen radical was involved in the electro-halogenation. In contrast, dimer condensation occurred via electrocatalysis rather than a Lewis base-induced haloform reaction.…”
Section: Resultsmentioning
confidence: 96%
“…Next, radical inhibition experiments were conducted in the presence of a stable oxyl-radical, 2,2,6,6-tetra-methyl-1-oxylpi-peridine (TEMPO) (Scheme 4D). 44 The results of these experiments showed that the electrocatalytic halogenation and dimer condensation processes were inhibited, indicating that a halogen radical was involved in the electro-halogenation. In contrast, dimer condensation occurred via electrocatalysis rather than a Lewis base-induced haloform reaction.…”
Section: Resultsmentioning
confidence: 96%
“…The Stern-Volmer plot was collected from furan solutions consisting of furan + maleic anhydride + O 2 , and furan + O 2 mixture (see details in ESI †). 42 The UV-VIS and fluorescent spectra of Ru(bpy) 3 Cl 2 were recorded. Ru(bpy) 3 Cl 2 showed an optical absorption maximum at 300 nm under the excitation wavelengths of 300 nm, and it showed an emission peak at l em = 320 nm.…”
Section: Mechanism Experimentsmentioning
confidence: 99%
“…Nevertheless, the strong acids in the CDs are not conducive to separation and inevitably affect the environment. 30…”
Section: Synthesis Of Cdsmentioning
confidence: 99%